Case study: Natural-Cosmetic Package Style from Milan - Laedpriwan, Sineenart (Fine Arts Journal: Srinakharinwirot University, 2011)
Package is the tool of product’s marketing distribution. Therefore, the research is to study package design’s trend in term of natural cosmetic from the countries’ leader of fashion such as Milan (Italy). Sampling tools are the natural product’s packages from the amount of 30 pieces. Founded, the cosmetic packages are mostly present the quality of natural product which is filled inside the bottle. 20% can be communicated in public by natural form. 30% presented by technique to be added in value and make them more interesting. 10% refer to the other aspect of communication such as styles, materials also patterns which are the elements of design. Product’s consumer can be classified in to 80% of the high education level women. Therefore, 90% of designers start to design by studying design’s trend which would be developed by the different location, society, climate etc. Production techniques can be the main idea in creating an interesting point to all packages. They are the most important choice for designer to make the different and variety of styles on to them. However, the second priority is the different in variety of shapes. The final aspect is the variety of graphics. Therefore, 60% of the designer focus on the functions of packages, 30% focus on the shapes and styles and only 10% focus on the graphics. By the way, most of the designer is very thoughtful of the investment for materials and processes which should be 3R: reuse, recycle and reduce to save the earth. In conclusion, Thai package designers mostly have intelligent and effort in creating all types of package for the natural-cosmetic products which is one of the most important export products from Thailand. However, it would be developed and assist the SME manufacturer to added the products value in order to compete with products from other countries. The product’s consumers in Milan are mainly respect for the brand of the cosmetic which can be referred to the quality of their sake. กรณีศึกษารูปแบบบรรจุภัณฑ์เครื่องสำอางส่วนผสมธรรมชาติจากกรุงมิลาน บรรจุภัณฑ์เป็นสื่อความเข้าใจและการนำเสนอผลิตภัณฑ์เพื่อการจัดจำหน่าย โครงการออกแบบบรรจุภัณฑ์เครื่อง สำอางสมุนไพรจึงได้จากการรวบรวมแนวโน้มในการออกแบบบรรจุภัณฑ์ที่จัดจำหน่ายในประเทศที่มีความก้าวหน้าในด้าน การออกแบบ คือ กรุงมิลานประเทศอิตาลีจากจำนวนกลุ่มตัวอย่างทั้งสิ้น 30 ชิ้น พบว่าบรรจุภัณฑ์เครื่องสำอางที่ได้จาก ส่วนผสมทางธรรมชาติมักสะท้อนความเป็นธรรมชาติเพื่อการสื่อความเข้าใจถึงคุณภาพของตัวผลิตภัณฑ์โดยจำนวนร้อยละ 45 สื่อความด้วยการเลือกใช้วัสดุที่มาจากธรรมชาติร้อยละ 20 สื่อความเข้าใจด้วยรูปทรงที่เป็นสัญลักษณ์ของธรรมชาติ และร้อยละ 30 สื่อความด้วยกราฟิกโดยใช้เทคนิคการพิมพ์เพื่อเพิ่มมูลค่าให้แก่สินค้าส่วนที่เหลือร้อยละ 10 สื่อความหมาย ด้วยวิธีอื่นๆ นักออกแบบเป็นผู้ที่มีความสำคัญในการส่งเสริมตัวผลิตภัณฑ์ให้มีคุณค่ามากขึ้นด้วยการวางแนวทางการ ออกแบบสร้างมูลค่าเพิ่มด้วยการจัดวางองค์ประกอบทางศิลปะอย่างมีมาตรฐานและเหมาะสมกับผู้บริโภคที่มีการศึกษาใน ระดับสูงที่พบว่าร้อยละ 80 เป็นผู้มีการศึกษาไม่ต่ำกว่าระดับปริญญาตรีจากการศึกษาพบว่านักออกแบบร้อยละ 90 เริ่ม ต้นหาข้อมูลด้วยการศึกษาแนวโน้มรูปแบบและความนิยมในปัจจุบันเพื่อใช้เป็นส่วนประกอบหลักในการออกแบบ โดยเล็ง เห็นว่าความชื่นชอบในตัวผลิตภัณฑ์นั้นมักสอดคล้องรสนิยมและความนิยมในแต่ละยุคสมัยทางสังคม เทคโนโลยีการผลิต เป็นส่วนหนึ่งที่มีผลต่อการออกแบบบรรจุภัณฑ์โดยเป็นส่วนทีสร้างความแปลกใหม่ให้แก่ผลงานนวัตกรรม ที่สามารถเห็นได้ ชัดเจนที่สุด ส่วนรูปทรงจะมีความชัดเจนเป็นรอง และที่น้อยที่สุดคือด้านกราฟิก การออกแบบสร้างสรรค์ผลงานโดยร้อยละ 60 เน้นประโยชน์ใช้สอยที่แตกต่าง ร้อยละ 30 สร้างความแตกต่างด้วยรูปทรง และร้อยละ 10 ใช้รูปแบบกราฟิกและสีสัน สร้างจุดสนใจ และใน ร้อยละ 80 มีความเห็นตรงกันด้านความคุ้มค่าของการลงทุนทั้งที่เป็นเรื่องของการใช้วัสดุและการ ผลิตหรือการสามารถนำกลับมาใช้ใหม่ได้อย่างเหมาะสม สรุปผลการดำเนินการวิจัย ผู้วิจัยพบว่านักออกแบบไทยมีความพร้อมที่จะออกแบบเพื่อการแข่งขันทางธุรกิจ กับ ต่างประเทศ โดยเฉพาะพัฒนาผลิตภัณฑ์เพื่อการส่งออกเป็นการเพิ่มผลผลิตให้กับวงการธุรกิจในอุตสาหกรรม ขนาดย่อม การยอมรับแนวโน้มทางด้านรูปแบบนั้นเป็นส่วนที่ทำให้เพิ่มยอดขายได้มากกว่า การพัฒนาบรรจุภัณฑ์และสร้างความเชื่อ ถือในการเป็นผู้เชี่ยวชาญทางความงามจึงเป็นสิ่งสำคัญอย่างยิ่งสำหรับตลาดเครื่องสำอางในดินแดนแถบตะวันตก โดย เฉพาะอย่างยิ่งในกรุงมิลาน ประเทศอิตาลีดินแดนแฟชั่นเสื้อผ้าและเครื่องสำอาง